Can kinematic and kinetic differences between planned and unplanned volleyball block jump-landings be associated with injury risk factors? - Mercado-Palomino, E.; Richards, J.; Molina-Molina, A.; Benitez, J. M.; Ureña Espa, A. (Gait and Posture, 2020)
Injury prevention programs for athletes are still limited by a lack of understanding of specific risk factors that can influence injuries within different sports. The majority of studies on volleyball have not considered the movement patterns when moving in different directions or in planned and unplanned block jump-landings. Methods: This study investigated all planes mechanics between the lead and trail limb when moving in dominant and non-dominant directions, for both planned and unplanned jump-landings in thirteen semi-professional female volleyball players. Ankle, knee and hip joint kinematics, kinetics and joint stiffness were recorded. Results: Our results showed statistically significant differences between the lead limb and the trail limb in the hip flexion angles, moments and velocity; in the knee flexion angles, moments, stiffness, power and energy absorption and in the ankle dorsiflexion, power and energy absorption, showing a tendency where the lead limb has a higher injury risk than the trail limb. When considering planned versus unplanned situations, there were statistically significant differences in knee flexion angles, moments, power and energy absorption; and hip contact angle, flexion angular velocity and energy absorption, with musculoskeletal adaptations in the planned situations. Discussion: It appears that the role of the limb, either lead or trail, is more important than the limb dominance when performing directional jump-landings, with the lead limb having a higher implication on possible overuse injuries than the trail limb. Furthermore, planned movements showed a difference in strategy indicating greater implications to possible overuse injuries than in the unplanned situations which may be associated with more conscious thought about the movements. Conclusion: Coaches should consider unilateral coordination training in both landing directions for the lead and trail limb, and should adapt training to replicate the competition environment, using unplanned situations to minimize asymmetries to might reduce injury risks.